2021
DOI: 10.1016/j.immuni.2021.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization potency of monoclonal antibodies recognizing dominant and subdominant epitopes on SARS-CoV-2 Spike is impacted by the B.1.1.7 variant

Abstract: Highlights d Potent nAbs were isolated from an asymptomatic donor with low plasma neutralization d RBD-specific nAbs target epitopes overlapping with known RBD antibody classes d NTD mutations in B.1.1.7 Spike confer neutralization resistance to NTD-specific nAbs d Most RBD-specific nAbs retain potent neutralization of the B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
183
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(211 citation statements)
references
References 100 publications
(119 reference statements)
20
183
0
2
Order By: Relevance
“…As would be predicted, the viral variants that contain mutations in RBD amino acids in the epitopes of mAbs, including therapeutic mAbs, can show partial or complete ablation of binding. Examples of such immune escape, including loss of neutralizing mAb activity, have been shown for B.1.1.7 ( Graham et al., 2021 ), B.1.351 ( Hoffmann et al., 2021 ; Li et al., 2021 ), P.1 ( Dejnirattisai et al., 2021b ; Hoffmann et al., 2021 ), B.1.427/B.1.429 ( McCallum et al., 2021b ), and B.1.617.2 ( Planas et al., 2021 ). We expect more data on the efficacy of vaccines and antibody-based therapeutics against these and other newly emerging SARS-CoV-2 variants to become available in the coming months.…”
Section: Antibody Responses To Viral Variantsmentioning
confidence: 96%
“…As would be predicted, the viral variants that contain mutations in RBD amino acids in the epitopes of mAbs, including therapeutic mAbs, can show partial or complete ablation of binding. Examples of such immune escape, including loss of neutralizing mAb activity, have been shown for B.1.1.7 ( Graham et al., 2021 ), B.1.351 ( Hoffmann et al., 2021 ; Li et al., 2021 ), P.1 ( Dejnirattisai et al., 2021b ; Hoffmann et al., 2021 ), B.1.427/B.1.429 ( McCallum et al., 2021b ), and B.1.617.2 ( Planas et al., 2021 ). We expect more data on the efficacy of vaccines and antibody-based therapeutics against these and other newly emerging SARS-CoV-2 variants to become available in the coming months.…”
Section: Antibody Responses To Viral Variantsmentioning
confidence: 96%
“…Studies with pseudoviruses and authentic SARS-CoV-2 containing variant substitutions suggested that adjustments to therapeutic antibody regimens might be necessary 1,2,[28][29][30] . Although our studies with variant strains in vivo suggest this conclusion likely holds for mAb monotherapy, four different mAb combinations performed well even when a virus was fully resistant to one mAb component.…”
Section: A C C E L E R a T E D A R T I C L Ementioning
confidence: 99%
“…S1c). This highlights the importance of the RBD as the major target for neutralising antibodies, whilst also underscoring the contribution of antibodies targeting regions outside of the RBD (for example the NTD of the spike protein 15,[29][30][31] ) to the neutralising antibody response, at the 5 month timepoint in this cohort. These data therefore revealed the persistence of detectable, albeit reduced, MBC specific for both spike and RBD in most people whose nAb titres against live virus had fallen below the threshold of detection.…”
Section: Sars-cov2 Spike and Rbd-specific Memory B Cells Can Persist After Loss Of Neutralising Antibodiesmentioning
confidence: 62%
“…To compare MBC frequencies in those who had maintained or lost nAb, we stained PBMC with SARS-CoV-2 spike trimer tetramers, made by pre-incubating recombinant biotinylated trimeric spike protein with fluorescently-conjugated streptavadin. 15 Dual staining with spike tetramers with two distinct fluorochromes was used to enhance the discrimination of true antigen-specific MBC (Fig.1c), as described previously. 2325 Frequencies of antigen-specific responses were calculated within the memory fraction of B cells (CD19 + CD20 + excluding IgD + , CD38 hi and CD21 + CD27 - naïve fractions, gating strategy in Fig.S1a, as previously described 26 ).…”
Section: Resultsmentioning
confidence: 99%